2005
DOI: 10.4103/0028-3886.15054
|View full text |Cite
|
Sign up to set email alerts
|

Frequent seizures and polytherapy can impair quality of life in persons with epilepsy

Abstract: Frequent seizures and polytherapy are associated with lower QOL in persons with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
70
4
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 17 publications
19
70
4
2
Order By: Relevance
“…The differences were highly statistically significant on ANOVA (p value<0.001).This shows that education improves quality of life. Similar results were reported by Choi-Kwon S et al 11 Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value <0.001), as also reported by Djibuti et al and Thomas et al 2,10 Duration of illness positively correlated with QOLIE-9 total scores (Pearson Correlation 0.118) and but was statistically insignificant (p value 0.242). Szaflarski et al found poor quality of life with increase duration of illness.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The differences were highly statistically significant on ANOVA (p value<0.001).This shows that education improves quality of life. Similar results were reported by Choi-Kwon S et al 11 Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value <0.001), as also reported by Djibuti et al and Thomas et al 2,10 Duration of illness positively correlated with QOLIE-9 total scores (Pearson Correlation 0.118) and but was statistically insignificant (p value 0.242). Szaflarski et al found poor quality of life with increase duration of illness.…”
Section: Discussionsupporting
confidence: 78%
“…2,6 Most of the previous studies on this topic were also carried out in large epilepsy centres. 5,7 Breier et al compared self-reported quality of life in patients with intractable epilepsy and pseudo seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Многие авторы отмечают, что при применении в качестве доба-вочной терапии ПЭП последнего поколения, отмечается лучший профиль переносимости политерапии [77,78]. Следует отметить, что есть и другие данные: согласно ис-следованиям, проведенным в разных странах [79][80][81] у больных эпилепсией, получавших политерапию, отмеча-лись более низкие показатели качества жизни (КЖ), а при переводе с политерапии на монотерапию показатели КЖ улучшались [78,82,83].…”
Section: вероятность эффективности терапии при первой неудачеunclassified
“…Even when the seizures cannot be controlled completely, a reduction in their frequency and severity can contribute immensely to enhancing the patient's quality of life and general wellbeing [10] [11] [12]. The rational use of antiepileptic drugs in settings with limited resources necessitate the evaluation and audit of their prescribing patterns in relation to efficacy in seizure control and patient wellbeing enhancement [11] [13]. The assessment and monitoring of care quality is necessary for health system capacity-building, decision-making and policy actions [13] [14].…”
Section: Introductionmentioning
confidence: 99%